The Association Between Pelvic Floor Muscle Force and General Strength and Fitness in Postpartum Women. Issue 6 (June 2020) - Moss, Whitney; Shaw, Janet M.; Yang, Meng; Sheng, Xiaoming; Hitchcock, Robert; Niederauer, Stefan; Packer, Diane; Nygaard, Ingrid E.
Abstract : Objective: The aim of the study was to determine whether measures of muscular strength and fitness are associated with pelvic floor muscle (PFM) force 1-year postpartum in a population of primiparous women who delivered vaginally. Methods: This cross-sectional analysis is an ancillary study to an ongoing prospective cohort study and includes 203 primiparous women. Procedures collected 1-year postpartum included maximal PFM force, grip strength, trunk flexor muscle endurance, percent body fat, intra-abdominal pressure during trunk flexor endurance testing, intra-abdominal pressure during strain, and self-reported physical activity. Results: The mean (SD) age was 29.8 (5.0) years and the mean (SD) body mass index was 24.5 (5.2) kg/m 2 . Nineteen percent were of Hispanic ethnicity. The median (interquartile range) PFM force was 5.05 (2.86–7.94) N. The median (interquartile range) trunk flexor endurance time was 146.0 (78.0–267.0), whereas the mean (SD) grip strength and percent fat were 32.4 (6.4) kg and 29.4% (10.0), respectively. There were no statistically significant associations between PFM force and any of the measures tested on analyses unadjusted or adjusted for self-report of doing PFM exercises. Of other factors evaluated, non-Hispanic ethnicity, increasing age, self-reported family history of pelvic organ prolapse or urinary incontinence, and normal and obese body mass index (both compared with overweight) were associated with lower PFM force. Conclusions: In primiparous women 1-year postpartum, we found no associations between PFM force and measures of strength and fitness. This study's results are consistent with existing literature that specific, targeted, and consistent pelvic floor exercises are the best way to improve PFM strength.